Strategies for Enhancing Qur’anic Literacy in Developing Outstanding Santri at Al-Amin Tarub Islamic Boarding School - Fauziyah, Sifa; Perawironegoro, Djamaluddin; Waharjani, Waharjani; Kholis, Nur; Hopid, Abdul (Journal of Indonesian Progressive Education, 2025)
This study is motivated by the limited understanding of Qur’anic literacy as merely a technical practice rather than a systematically managed institutional strategy in Islamic boarding schools. The research problem addressed in this study is how strategies to improve Qur’anic literacy skills are implemented at Pondok Pesantren Al-Amin Tarub Tegal. This study aims to describe and analyze these strategies within an institutional context. The research employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, and analyzed thematically. The findings reveal that strategies for improving Qur’anic literacy are implemented through vision-based planning, gradual implementation (tadarruj) through structured habituation, and integrated evaluation combining academic and character aspects. These strategies are supported by a conducive religious environment and active involvement of all elements within the pesantren. In conclusion, improving Qur’anic literacy skills can be effectively achieved through well-planned, systematic, and value-based strategies, contributing to the development of students’ cognitive, affective, and spiritual dimensions.